Medical adhesive compositions
By using less than 20% calcium silicate and lithium salt in medical adhesive composition, the problem of adhesive weakening dentin and inconvenient operation in the endodontic treatment is solved, and the effect of high biological activity and low compressive strength is achieved, which facilitates long-term stability and retreatment of teeth.
Patent Information
- Application Number
- CN202111111104.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-21
- Filing Date
- 2021-09-18
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-09-18
AI Technical Summary
Existing medical adhesive compositions have problems in dentin reduction, prolonged sclerosis inconvenience, and structural weakening under the action of saliva or inflammatory products in the treatment of pulp.
A medical adhesive composition is provided, comprising less than 20% calcium silicate and lithium salts of the total weight of the composition, in a premixed form, for easy handling, and with low compressive strength and high biological activity upon hardening.
Excellent volume stability and high biological activity in pulp treatment are achieved, reducing the risk of dentin weakening, facilitating retreatment, and improving the convenience of operation.
Smart Images

Figure CN114246803B_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a medical cement composition, and more particularly to a medical cement composition for filling a space from which nerves, blood vessels, cell tissues, hard tissues, etc. have been removed. [Background technology]
[0002] Generally, a medical filler composition, a material for filling a space from which nerves, blood vessels, cell tissues, hard tissues, etc. have been removed for therapeutic purposes, has been used in various fields.
[0003] Medical adhesive compositions are indispensable in the dental field, especially in the field of endodontics, where nerves, blood vessels and other tissues within a tooth are removed and the space is filled and sealed with a material to maintain the function of the tooth.
[0004] As a type of medical adhesive composition, mineral trioxide aggregate (MTA) is widely used in endodontic treatment, mainly used as a material for root canal perforation repair, pulpotomy, partial pulpotomy, pulp capping, root canal filling, root canal end reverse root filling, etc. MTA has the advantages of excellent sealing properties and biocompatibility, and is superior to calcium hydroxide, which is mainly used to treat living pulp, in terms of the formation of tertiary dentin or inflammatory cell infiltration.
[0005] Generally, MTA contains calcium silicate, calcium aluminate and gypsum as main components, similar to Portland cement. When calcium silicate reacts with water in the presence of body fluids, saliva, other liquids, etc., calcium silicate hydrate (CSH) and calcium hydroxide are produced.
[0006] Calcium silicate hydrate (CSH) has various shapes, including coarse fibrous crystals and irregular and twisted networks. Calcium silicate hydrate (CSH) has a layer structure with a very high surface area and colloidal internal voids, and calcium silicate hydrate (CSH) occupies about 50% to 60% by volume of the hardened product of MTA.
[0007] On the other hand, calcium hydroxide has hexagonal plate-like crystals and occupies about 20 to 25 volume % of the hardened product of MTA. The amount of calcium hydroxide is related to the type of calcium silicate contained in MTA and the degree of hydration reaction.
[0008] MTA has attracted much attention due to its high level of sealing properties and biocompatibility, showing revolutionary clinical results in many cases that were difficult to treat before MTA, but there is a problem that MTA may weaken dentin because MTA causes calcium hydroxide formation.
[0009] As is the case with ordinary calcium hydroxide preparations, if MTA is used to perform root canal filling, the likelihood of root fracture increases and dentin is physically removed during endodontic treatment, making the long-term prognosis of endodontic treatment poor.
[0010] To solve this problem, U.S. Patent No. 8,801,846 proposes a technique for neutralizing calcium hydroxide containing pozzolanic materials.
[0011] MTA has better sealing properties than conventionally used amalgam, IRM and super EBA, but has problems in that it takes a long time to harden, is inconvenient to operate, and causes discoloration. In addition, there is also a problem that MTA is greatly affected by the surrounding acidic environment during the hydration of MTA, thereby weakening the physical properties and structure of MTA. Even after MTA hardens, when the hardened product of MTA is exposed to saliva or inflammatory products in the oral cavity, the saliva or inflammatory products react with calcium hydroxide in MTA, thereby rapidly weakening the structure and deteriorating the sealing properties.
[0012] This is because when calcium hydroxide reacts with saliva or inflammatory exudate, it produces calcium sulfate, sodium hydroxide, and magnesium hydroxide, which increase the volume and corresponding expansion pressure.
[0013] In fact, the molar volume of calcium hydroxide is 33.2 cm 3 , and the molar volume of calcium sulfate is 74.2 cm 3 . Therefore, when calcium hydroxide is converted to calcium sulfate, the volume increases by about 2.2 times.
[0014] In addition, calcium sulfate is further reacted with calcium aluminate hydrate, monosulfate and tricalcium aluminate (C 3 A) reacts to form ettringite. In this process, the volume also increases, which creates expansion pressure and leads to cracks in the hardened product. This is known in the art as an alkali-aggregation reaction (AAR).
[0015] To solve this problem, research has been conducted in the art so far, focusing on a method of neutralizing calcium hydroxide using a pozzolan reaction, in which silicon dioxide and aluminum oxide active components react with calcium hydroxide in the presence of water to generate calcium silicate hydrate. Although the pozzolan reaction has the advantage that durability can be improved and sealing properties can be better, the pozzolan reaction has little effect on bioactivity or biocompatibility.
[0016] In addition, endodontic treatment is a treatment for sterilizing and sealing a complex dental pulp system. Despite the development of equipment and materials, it is known that it is very difficult to completely sterilize and seal the dental pulp system inside a tooth. Specifically, the medical adhesive composition used for endodontic treatment should be easily removed when retreatment is required due to reinfection or the like, even after it is completely hardened after the process is completed.
[0017] In order to improve the convenience of retreatment, US Pat. No. 9,445,973 proposes a technology relating to a removable adhesive composition for root canal filling, the removable adhesive composition containing 45% or more of zirconium oxide in the total amount of the composition.
[0018] As another biggest disadvantage of MTA, MTA is not easy to handle during the process. In order to overcome this disadvantage, US Pat. No. 9,668,825 discloses a technology for providing MTA in a premixed form.
[0019] In view of the technological development trends to date, there is still a need to develop a medical adhesive composition that satisfies all of the following three conditions when used in the human body.
[0020] 1) Excellent long-term stability achieved by suppressing delayed expansion caused by calcium hydroxide.
[0021] 2) Low compressive strength, enabling retreatment.
[0022] 3) High biological activity.
[0023]
Related technical documents
[0024] [Patent Literature]
[0025] (Patent Document 1) U.S. Patent No. 8801846
[0026] (Patent Document 2) U.S. Patent No. 9445973
[0027] (Patent Document 3) U.S. Patent No. 9,668,825 [Summary of the invention]
[0028]
Technical issues
[0029] An object of the present disclosure is to provide a medical adhesive composition having low compressive strength and low calcium hydroxide productivity to achieve excellent volume stability and high bioactivity.
[0030] In particular, low compressive strength of the medical adhesive composition is a very useful property when retreatment is required due to infection after treatment.
[0031]
Technical Solution
[0032] The present disclosure provides a medical adhesive composition comprising less than 20 wt % of calcium silicate based on the total weight of the composition; and a lithium salt.
[0033]
Beneficial Effects
[0034] The medical adhesive composition of the present disclosure can be provided in a premixed state. Therefore, it is easy to apply the medical adhesive composition during treatment. In addition, the medical adhesive composition of the present disclosure has a low compressive strength after hardening. Therefore, it is easy to remove the medical adhesive composition when re-treatment is required. In addition, the medical adhesive composition of the present disclosure has excellent volume stability and high biological activity.
Brief Description of the Drawings
[0035] FIG. 1 shows the measurement results of the compressive strength of the hardened products of the medical adhesive compositions prepared according to Example 1 and Comparative Example 2. FIG.
[0036] Figure 2 The results of using the hardened products of the medical adhesive compositions prepared according to Preparation Example 1 and Examples 1 to 7 for a cytotoxicity test are shown. [Specific implementation method]
[0037] Hereinafter, embodiments and examples of the present disclosure will be described in detail with reference to the accompanying drawings so that a person skilled in the art can easily implement the present disclosure. However, it should be noted that the present disclosure is not limited to the embodiments and examples to be described below, and can be embodied in many different forms. In the accompanying drawings, parts not related to the description are omitted to clearly illustrate the present disclosure.
[0038] Throughout the specification, when any component “includes” or “comprises” any elements, it means that other elements are not excluded but may further include other elements unless explicitly stated otherwise.
[0039] Throughout the specification, the term "about" is used to indicate "at" or "close to" a value when manufacturing tolerances and material tolerances are inherent in the circumstances, and to prevent the precise or absolute values disclosed to facilitate understanding of the present disclosure from being illegally or unfairly used by unlawful infringers.
[0040] Although endodontic treatment is designed to treat teeth with complex and varied anatomical shapes, and requires a long treatment period and complex equipment, its success rate is often unsatisfactory. If the first treatment is unsuccessful, more nerve treatment or root canal end surgery is often required before extraction.
[0041] For this retreatment, it is necessary to remove the filling material used in the previous operation. At this time, if the root canal filling material is too hard, it is difficult to remove the filling material using the method commonly used by dentists, thereby causing difficulty in retreatment.
[0042] That is, it is necessary to appropriately reduce the compressive strength of the hardened filling material so that the hardened filling material can be removed when retreatment is required.
[0043] The medical adhesive composition of the present disclosure may include less than 20 wt % calcium silicate, preferably 5 wt % or more and less than 20 wt % calcium silicate, based on the total weight of the composition.The calcium silicate may be water-curable.
[0044] When the calcium silicate content is less than 5 wt % of the total weight of the adhesive composition, the adhesive composition greatly deteriorates not only in physical properties such as strength and sealing properties but also in biological activity, and is thus not suitable for medical use.
[0045] When the calcium silicate content is 20 wt% or more based on the total weight of the composition, the adhesive composition has high compressive strength, making it difficult to remove for re-treatment.
[0046] Generally, regarding MTA compositions, it has been known that the unique biological activity of MTA is exhibited only when the calcium silicate content is at least 20 wt % or more based on the total weight of MTA.
[0047] It has been understood that the expression of biological activity is mainly affected by ionized calcium hydroxide, which is a product produced by the hydration reaction of calcium silicate having hydration properties.
[0048] On the other hand, calcium hydroxide weakens the collagen fibers of the tooth root over a long period of time, thereby causing a problem of reduced fracture resistance of the tooth root, and causes delayed expansion due to alkali-aggregation reaction (AAR) after hardening in vivo.
[0049] Therefore, in order to reduce the absolute amount of calcium hydroxide produced as a product of the hydration reaction, an additive capable of increasing biological activity while reducing the amount of calcium silicate having hydration properties is required.
[0050] The medical adhesive composition of the present disclosure may also include 1.5 wt% or less of lithium salt based on 100 wt% of calcium silicate, wherein the calcium silicate is included in the medical adhesive composition in an amount of less than 20 wt%. Preferably, the content of the lithium salt may be greater than or equal to 0.1 wt% or less than or equal to 1.5 wt%.
[0051] The lithium salt supplements the bioactivity of the medical adhesive and at the same time increases the long-term volume stability of the medical adhesive after hardening in the human body.
[0052] When the lithium salt is used in an amount of less than 0.1 wt %, the lithium salt has little effect in supplementing the biological activity of calcium silicate and inhibiting the alkali aggregation reaction (AAR) of calcium silicate. When the lithium salt is used in an amount of more than 1.5 wt %, the biological activity of the medical adhesive composition becomes poor, thereby increasing the production cost.
[0053] Furthermore, the lithium salt may be any one or more selected from the group consisting of lithium silicate, lithium nitride, lithium carbonate, and lithium hydroxide.
[0054] The calcium silicate disclosed herein may be tricalcium silicate (C 3 S). Specifically, pure tricalcium silicate may be pre-synthesized for use in the preparation of the medical adhesive composition. Since pure tricalcium silicate forms a filling product having high compressive strength through its hydration reaction, if the amount of pure tricalcium silicate included is 20% or more of the total weight of the medical adhesive composition, it may be difficult to remove the filling product after hardening.
[0055] The compressive strength of the medical adhesive composition of the present disclosure may preferably be greater than or equal to 3 MPa and less than or equal to 12 MPa, so as to facilitate removal for re-treatment, etc. When the compressive strength is less than 3 MPa, the strength is low, so that the hardened product of the medical adhesive composition is fragile even if it is subjected to a small impact after the process. On the other hand, when the compressive strength is greater than 12 MPa, it is not easy to remove the hardened product of the medical adhesive composition for re-treatment.
[0056] In addition, the medical adhesive composition of the present disclosure may further comprise any one or more substances selected from the following as a liquid component: N-methyl-2-pyrrolidone (NMP), dimethylsulfoxide (DMSO), and diethylene glycol monoethyl ether (DEGEE).
[0057] However, the liquid component is not particularly limited thereto, provided that the liquid component is an anhydrous liquid having low cytotoxicity and at the same time has low viscosity in a polar solvent, is easily miscible with water, has penetration enhancing properties, and can be safely used in the human body.
[0058] Furthermore, the medical adhesive composition of the present disclosure preferably has radiopacity so that the progress of the process can be accurately checked via observation by radiographic examination. To this end, it is preferred that the medical adhesive composition of the present disclosure further comprises a radiopaque powder.
[0059] The radiopaque powder preferably comprises one or more selected from the group consisting of ferroelectrics, tungsten oxide, calcium tungstate, zirconium oxide, tantalum pentoxide, bismuth subnitrate and barium sulfate.
[0060] Meanwhile, the radiopaque powder is preferably included in a suitable amount according to the use of the medical adhesive composition of the present disclosure and the type of the radiopaque powder.
[0061] More specifically, it is preferred that the radiopaque powder is contained in an amount of 40 to 60 wt % based on the total weight of the medical adhesive composition.
[0062] Meanwhile, the medical adhesive composition of the present disclosure preferably comprises one or more selected from the following as a thickener: methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol and polyvinyl pyrrolidone, and the thickener is used to control the rheological properties of the medical adhesive composition by imparting an appropriate viscosity to the medical adhesive composition.
[0063] In order to make the medical adhesive composition into a paste, the content of the liquid component and the thickener in the medical adhesive composition of the present disclosure is preferably 15 wt % to 35 wt % relative to the total weight of the medical adhesive composition. This is because when their content is less than 15 wt %, it is difficult to make the medical adhesive composition into a paste for kneading, and when their content is greater than 35 wt %, there is a problem that the powder component is separated due to the excess liquid component.
[0064] In addition, the calcium silicate may have a size of 2 μm or less. When the size of the calcium silicate is greater than 2 μm, it may aggregate in the root canal, causing a problem of hindering the advancement of the GP cone.
[0065] The medical adhesive composition of the present disclosure can be a dental adhesive composition. Specifically, the medical adhesive composition of the present disclosure can be used for pulp capping, pulpotomy, reverse root filling, perforation repair, root canal filling, etc.
[0066] Meanwhile, the medical adhesive composition of the present disclosure is preferably formed into a paste type to facilitate injection into spaces that require in vivo repair and filling and to facilitate storage. To this end, the medical adhesive composition of the present disclosure preferably contains a liquid material. That is, the medical adhesive composition of the present disclosure has a paste form by mixing and kneading a solid component with a liquid component.
[0067] Furthermore, the medical adhesive compositions of the present disclosure may be provided in a premixed form.
[0068] Hereinafter, the present disclosure will be described in more detail using preparation examples, comparative examples and examples. All reagents used herein are generally commercially available and, unless otherwise indicated, do not require special purification when used. In addition, the following preparation examples, comparative examples and examples are only used to illustrate the present disclosure and are not intended to limit the scope of the present disclosure.
[0069] Preparation Example 1
[0070] 2 parts of hydroxypropyl methylcellulose were added to the DMSO solution and completely dissolved in the DMSO solution. Thereafter, the DMSO solution and the powder component were kneaded in a weight ratio of 3:10, and the powder component was prepared by mixing tricalcium silicate and zirconium oxide (ZrO 2 ) is obtained, and a lithium salt additive is added in a controlled amount to prepare a medical adhesive composition.
[0071] (The tricalcium silicate content of the prepared medical adhesive composition was 9.6 wt % of the total weight of the composition.)
[0072] Example 1 to Example 7
[0073] The medical adhesive composition was prepared according to the preparation method of Preparation Example 1, except that the lithium salt (lithium carbonate) content of the medical adhesive composition was 0.3 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.9 wt%, 1.2 wt% and 1.5 wt%, respectively, based on 100 wt% of calcium silicate of the medical adhesive composition, as shown in Table 1 below.
[0074] [Table 1]
[0075] Example Lithium salt (lithium carbonate) content (weight %) 1 0.3 2 0.5 3 0.6 4 0.7 5 0.9 6 1.2 7 1.5
[0076] Comparative Example 1
[0077] The medical adhesive composition was prepared according to the preparation method of Preparation Example 1, except that the powder component was prepared by mixing tricalcium silicate and zirconium oxide (ZrO 2 That is, Comparative Example 1 does not contain a lithium salt.
[0078] (The tricalcium silicate content of the prepared medical adhesive composition was 20.03 wt % of the total weight of the composition.)
[0079] Test Example 1 (Compressive Strength)
[0080] Respective specimens of the hardened products of the medical adhesive compositions of Example 1 and Comparative Example 1 were prepared, and the compressive strength of the specimens was measured (two specimens were prepared and measured in Example 1, and four specimens were prepared and measured in Comparative Example 1).
[0081] To measure the compressive strength, each of the prepared samples was implanted in a 10 mm*10 mm*10 mm square groove in an acrylic mold, and then the acrylic mold containing the sample was placed in a constant temperature and humidity chamber under conditions of 36.5° C. and 100% of RH to harden the sample.
[0082] Thereafter, the compressive strength of each of the test specimens was measured using a universal testing machine (model name: Instron 5882). During the measurement, the maximum load was set to 5000 N, and the crosshead speed was set to 0.85 mm / min.
[0083] The measurement results are shown in Figure 1.
[0084] As shown in FIG. 1A , the hardened product of Example 1, corresponding to a medical adhesive composition having a lithium salt content of 0.3 wt % relative to the calcium silicate content, had a measured average compressive strength of about 5.034 MPa.
[0085] In contrast, as shown in FIG. 1B , the hardened product of Comparative Example 1 had a measured average compressive strength of about 12.374 MPa.
[0086] That is, the lower the content of calcium silicate (tricalcium silicate), the lower the compressive strength. When the calcium silicate content is greater than or equal to 20 wt %, as in Comparative Example 1, the compressive strength is shown to exceed 12 MPa, and the resulting hardened product may not be easily removed when re-treatment is required.
[0087] Thus, it has been found that in order to maintain the compressive strength of the hardened product produced at a suitably low level in view of the need for retreatment, the calcium silicate content should be maintained at less than 20% by weight of the total weight of the medical adhesive.
[0088] Test Example 2 (Cytotoxicity)
[0089] The cytotoxicity of the hardened product of the medical adhesive composition was tested using the MTT assay. The specific test method will be described below.
[0090] After preparing the hardened product of the medical adhesive composition into a specimen having a diameter of 10 mm and a thickness of 2 mm, the specimen was stored in an incubator at 37° C. under constant humidity for 3 to 7 days. Thereafter, the specimen was exposed to ultraviolet light overnight for sterilization, and then placed in an incubator at 37° C. at 0.5 cm 2 The cells were extracted at a concentration of 1.5 × 10 / ml for 3 days, and the supernatant of the extracted culture medium was separated and stored. The MC3T3-E1 cell line to be used for cytotoxicity test was cultured in MEM-α medium supplemented with 10% FBS.4 The cells were aliquoted into 24-well plates at a rate of 10 cells / well and cultured for one day. At this time, samples were prepared in quadruplicate, and corresponding plates for the 1st, 2nd and 3rd days were prepared. Thereafter, the culture medium was removed from the cultured cell line, and the extracted culture medium was aliquoted and cultured in an amount of 1 ml / well, and the MTT assay was performed on the 1st, 2nd and 3rd days. First, the cell culture medium was removed, and each sample was treated with a 0.05% MTT solution dissolved in PBS in an amount of 200 μm, and then cultured in an incubator at 37°C for 2 hours. Thereafter, a DMSO solution was added to each sample in an amount of 200 μm. After 10 minutes, 200 μm of each sample was placed in a 96-well plate, and the optical density (OD) was measured to evaluate cell viability. Here, the mean and standard deviation of the measurements between the three test groups were used to determine the cell viability.
[0091] The results of testing the cytotoxicity of the hardened product of the medical adhesive composition by MTT assay are shown in Figure 2 middle.
[0092] Figure 2 The cell viability of a control (CON) of a hardened product to which no medical adhesive composition was applied, a hardened product of a medical adhesive composition not containing a lithium salt (OES, corresponding to Preparation Example 1), and hardened products of the medical adhesive compositions in Examples 1 to 7 (with lithium salt contents of 0.3 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.9 wt%, 1.2 wt% and 1.5 wt%, respectively, based on 100 wt% of tricalcium silicate) are shown.
[0093] ( Figure 2 The graph shows the results of measuring the cell viability in the hardened product of the medical adhesive composition, and the bar values represent CON, OES, and 0.3 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.9 wt%, 1.2 wt%, and 1.5 wt% lithium salt content from left to right, respectively. )
[0094] First, the cell viability changes over time. However, it was confirmed that the cell viability in the hardened product of the medical adhesive composition without lithium salt was much lower than that in the hardened product of the medical adhesive composition containing lithium salt. This became more obvious over time. It was also confirmed that even after at least 3 days, the biological activity was maintained to increase according to the increase in the lithium salt content.
[0095] In addition, as a result of measurement over time, it was shown on the 3rd day that the cell activity was particularly high in the hardened products of the medical adhesive compositions having a lithium salt content of 0.5 wt % to 0.9 wt %, and was slightly lower in the hardened products of the medical adhesive compositions having a lithium salt content of 0.3 wt % and 0.9 wt % to 1.5 wt %.
[0096] From the above test results, it was found that the cell activity in the medical adhesive composition containing less than 20 wt% of calcium silicate can be improved by adding lithium salt. In addition, it was confirmed that the cell activity can be optimized when the lithium salt content in the medical adhesive composition is 1.5 wt% or less.
[0097] That is, it was found that the cell activity in the hardened product of the medical adhesive composition of the present disclosure was very good.
[0098] The embodiments of the medical adhesive composition disclosed herein are merely preferred embodiments that make it easy for a person of ordinary skill in the art to which the disclosure belongs to implement the disclosure, and the disclosure is not limited to the above embodiments and drawings, and therefore the scope of the disclosure is not limited thereto. Therefore, it should be understood that the true technical protection scope of the disclosure is defined by the technical spirit of the appended claims. In addition, it is obvious to those skilled in the art that various substitutions, modifications and changes can be made without departing from the technical spirit of the disclosure, and the substitutions, modifications and changes fall within the scope of the disclosure.
Claims
1. A medical adhesive composition, comprising: Calcium silicate, the amount of calcium silicate is 5 wt% or more and less than 20 wt% of the total weight of the composition; a lithium salt in an amount of 0.1 wt % or more and 1.5 wt % or less based on 100 wt % of the calcium silicate; and Any one or more selected from the group consisting of methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol and polyvinyl pyrrolidone; and in, The calcium silicate is tricalcium silicate; wherein the tricalcium silicate is pre-synthesized for use in the preparation of a medical adhesive composition; and Wherein, the lithium salt increases the biological activity of the medical adhesive.
2. The medical adhesive composition according to claim 1, wherein the lithium salt is any one or more selected from the group consisting of lithium silicate, lithium nitride, lithium carbonate and lithium hydroxide. 3 . The medical adhesive composition according to claim 1 , wherein the compressive strength of the medical adhesive composition after hardening is greater than or equal to 3 MPa and less than or equal to 12 MPa.
4. The medical adhesive composition according to claim 1, further comprising any one or more selected from the group consisting of N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO) and diethylene glycol monoethyl ether (DEGEE).
5. The medical adhesive composition of claim 1, wherein the medical adhesive composition is premixed.
Citation Information
Patent Citations
Self-neutralising type of calcium hydroxide preparation for use in dentistry
US8801846B2
Dental filling composition comprising zirconia powder
US9445973B2
Dental and endodontic filling materials and methods
US9668825B2
Medical filler composition
CN111295174A
Very fast setting cementitious composition with high early-age compressive strength
US20080302276A1